Pengembangan Sistim LEISA untuk Meningkatkan Produktivitas dan Kualitas Umbi Kentang (Solanum Tuberosum L.) - Yohanes Setiyo; Ketut Budi Susrusa; I G.A. Lani Triani; I D.G. Mayun Permana (Fakultas Teknologi Pertanian, Universitas Udayana Gedung GA, Fakultas Teknologi Pertanian, Universitas Udayana Jl. Raya Bukit Jimbaran, Jimbaran, Kuta Selatan, Bali Telp/Fax: (0361) 701801, 2016)
The research objective of applications LEISA (Low External Input on Sustainable Agriculture)system on the cultivation of potatoes was to increase productivity and quality of potatoes tubers.The experiment was designed with a randomized block design (CRD) with six treatments ofchicken manure compost fertilizer dosage. Dose fertilizing compost are: 0 ton/ha (as control), 10tons/ha, 12.5 tons/ha, 15 tons/ha, and 17.5 tons/ha and 20 tons/ha. This fertilizer was combinedwith NPK fertilizer 250 kg/ha. Parameters measured were: the physical properties of the soil, landfertility, the population of bacteria in the soil, land productivity and quality of potato tubers.LEISA systems with dose of compost 20 tons/ha are able to produce potatoes to 30.7 tons/ha or1.17 kg/tree. Total consumption of potato tuber from the research was 76.84 - 87.71%, while theclass of seed potatoes was 9.25 - 22.06%. Porosity of the soil was more than 50% with the abilityof soil to retain water 28 % w.b at doses of chicken manure fertilizer compost 15 tons/ha. At thisdose soil organic matter content of more than 5% with CEC was 23.8 me/100g or land wascategorized fertile soil. In addition, at pH close to neutral (6.8 to 6.9) existing bacterial populationwas 2.2 x 103 - 4.7 x 108 cfu.